Sistem Informasi Persebaran Penyakit Demam Berdarah di Kota Madiun Menggunakan Algoritma K-Means - Gita Lely Endika Putri; Ida Widaningrum; Dyah Mustikasari (Jurnal Informatika Universitas Pamulang, 2021)
One type of disease that often causes extraordinary events (KLB) in Indonesia is dengue fever. This also happened in Madiun City, one of the areas where the spread of Dengue Fever has consistently grown rapidly. Information obtained from the Madiun City Health and Family Planning Office from 2013 to 2020 shows that in 2020 there was a remarkable increase after experiencing a decline in 2017. The process of direct socialization to the community is still difficult, and there is no web-based mapping of the spread of dengue fever in Madiun. Therefore, this study builds a web-based geographic information system for the spread of dengue fever using PHP and SQL. It is hoped that this geographic information system can help related parties to make it easier to convey information about the spread of dengue fever, especially within the Madiun City area, and as an effort to anticipate the expansion of its distribution area. The identification of regional groups in this system is divided into categories, namely Endemic, Sporadic, Potential, and Free. Grouping, using clustering method based on K-Means logic. The result is that the geographic information system can display a map of the distribution of dengue fever in Madiun City. There is one kelurahan with Potential status, 14 kelurahan with Sporadic status, and 12 kelurahan with Endemic status.